STATUS HUKUM ASET DIGITAL SEBAGAI BARANG MILIK DALAM PERSPEKTIF HUKUM INDONESIA - Wijaya, Komang Adi; Dewi, Kadek Ary Purnama; Dewi, Cokorde Istri Dian Laksmi (RIO LAW JURNAL, 2025)
The advancement of digital technology has led to the emergence of digital assets such as cryptocurrencies and Non-Fungible Tokens (NFTs), which hold significant economic value in society. However, within Indonesia's legal system, the legal status of digital assets as objects of ownership remains undefined. This study aims to analyze the legal status of digital assets as property under Indonesian civil law, examine the regulations governing their ownership, and identify legal challenges related to the recognition and protection of digital assets. This research employs a normative legal method with a qualitative approach, analyzed through content analysis and interpretation of legal norms. The findings indicate that digital assets can be categorized as intangible movable objects that potentially qualify as property, although they currently lack comprehensive legal grounding. Regulatory fragmentation, dual supervision, and weak legal protection present major obstacles to ensuring legal certainty for digital asset holders. Therefore, an integrated and responsive legal framework is needed to regulate ownership and provide legal protection for digital assets in Indonesia.Keywords: digital assets, property law, ownership